The Evening News - Ardizzone, Tony (Book collections on Project MUSE., 1986)
Tony Ardizzone writes of the moments in our lives that shine, that burn in the dim expanse of memory with the intensity and vivid light of the evening news. The men and women in these stories tend to arrange their days, order their pasts, plan their futures in the light of such moments, finding epiphanies in the glowing memory of a father's laugh or a mother's repeated story, in a broken date or a rained-out ball game. Set mostly in Chicago's blue-collar neighborhoods, these stories focus on subjects that concern us all: disease and death, vandalism and sacrilege, rape and infidelity, lost lov.